SELECTIVE AORTIC ARCH PERFUSION FOR THE REVERSAL OF HAEMORRHAGE-INDUCED TRAUMATIC CARDIAC ARREST IN A SWINE MODEL OF NON-COMPRESSIBLE TORSO HAEMORRHAGE. Issue 12 (18th November 2016) - Barnard, EB; Smith, JE; Manning, JE; Rall, JM; Cox, JM; Bebarta, VS; Ross, JD
Abstract : Objectives & Background: Haemorrhage is the leading cause of potentially survivable trauma death. Selective Aortic Arch Perfusion (SAAP) is an experimental resuscitative intervention that has the potential to improve trauma survival: a trans-femoral intra-aortic balloon controls torso haemorrhage, while the catheter's large central lumen allows oxygenated blood to be delivered to the proximal aorta–theoretically providing coronary perfusion pressures adequate for return of spontaneous circulation in cardiac arrest (figure 1). Hypothesis–In haemorrhage-induced traumatic cardiac arrest, SAAP with oxygenated blood will infer a short-term survival advantage over both closed chest compressions (CPR) with intravenous blood, and Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) with intravenous blood. Methods: 70–90 kg swine underwent a non-compressible torso haemorrhage (NCTH) and controlled arterial haemorrhage. Arrest was defined as a systolic blood pressure (SBP) <10 mm Hg, together with an inappropriate bradycardia. Animals were allocated to one of three groups: CPR with four units of intravenous blood, REBOA with four units of intravenous blood, and fresh whole blood SAAP (FWB-SAAP) with 1600 ml of oxygenated intra-aortic blood. Primary outcome was 60-minute 'pre-hospital' survival. Data are described as mean (+/− standard devation). Multi-group analyses were by ANOVA, and survival was analysed by Log-rank (Mantel-Cox) test. Results: There were ten animals per group, a total of 30 swine. Mean weight of 79.9 kg (+/−5.5) p=0.3. Mean time from the start of the injury to onset of arrest was 11.2 minutes (+/−1.9) p=0.2. Prior to intervention the mean SBP was 2.9 mm Hg (+/−3.2) p=0.7, and the mean heart rate was 41 bpm (+/−32) p=0.5. Primary outcome – FWB-SAAP demonstrated an 80% 60-minute 'pre-hospital' survival, compared to 10% with CPR, and 0% with REBOA, p<0.001 (figure 2). Conclusion: In this swine model of haemorrhage-induced traumatic cardiac arrest with NCTH, SAAP infers a short-term survival advantage over both conventional therapy (CPR), and over evolving therapy (REBOA). Of note, SAAP induced return of spontaneous circulation from cardiac electrical asystole.Figure 1 Figure 2